Approximate solutions some nonlinear evolutions equations by using the reduced differential transform method - Ibis, Birol; Bayram, Mustafa (International Journal of Applied Mathematical Research, 2012)
In this paper, the reduced differential transform method (RDTM) is applied to various nonlinear evolution equations, Kortewegde Vries Burgers' (KdVB) equation, DrinefeldSokolovWilson equations, coupled Burgers equations and modified Boussinesq equation. Approximate solutions obtained by the RDTM are compared with the exact solutions. The present results are in good agreement with the exact solutions. Comparisons show that the RDTM is capable of solving effectively a large number of nonlinear evolution equations with high accuracy.Â